PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI KEGUNAAN, dan PENGALAMAN TERHADAP MINAT WAJIB PAJAK MENGGUNAKAN SISTEM E-FILING (Studi Kasus Wajib Pajak Orang Pribadi Di Kabupaten Pati) - Nanik Ermawati; Zamrud Mirah Delima (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2016)
E-Filing is one of the technological developments in the modern era, in which the taxpayer is easy to report to the tax office use online. This study aims to determine the effect of perceived ease of use, perceived usefulness, andexperience to the interest of individual taxpayers to use the E-Filing. Research was conducted on an individual taxpayer in Pati regency. The method used regression analysis. The data used in this study are primary data, using a questionnaire. the results of this study indicate that the perceived ease of use, perceived usefulness, and experience affect the interest of taxpayers to use the E-Filing.